Estrategias educativas de lectura para mejorar los niveles de comprensión lectora de los alumnos del 3° grado del nivel primario en la Institución Educativa Ruy Guzmán Hidalgo 2020 - Perdomo Rodriguez, Maria Luisa (2024)
Improving reading comprehension via the adoption of instructional reading methods is the goal of this explanatory research with a quasi-experimental design in third graders at the primary level. An investigation on the efficacy of instructional reading practices in enhancing third-grade primary school pupils' reading comprehension at the Ruy Guzmán Hidalgo Educational Institution in 2020. Therefore, the sample selection is 30 in a single experimental group. The findings show that in the pretest of the experimental group, 56.7% of the children showed some reading comprehension, 33.7% demonstrated some progress, and 10.0% achieved proficiency. In the experimental group, 6.7% of the students showed some reading comprehension at the beginning of the test, 33.3% were in process, and 60.0% had achieved reading comprehension ability, according to subsequent results. to the test. By comparing the results of the pre- and post-tests administered to the sample of students, we were able to find evidence supporting the null hypothesis. As a result, we can say that 60% (18 students) reached the achieved level of reading comprehension after implementing the educational strategies program. This finding indicates a highly significant relationship, suggesting that the program helped improve students' reading comprehension.